2005
DOI: 10.1097/01.shk.0000183431.78973.cd
|View full text |Cite
|
Sign up to set email alerts
|

Murine in Vivo Myocardial Contractile Dysfunction After Burn Injury Is Exacerbated by Pneumonia Sepsis

Abstract: We evaluated hemodynamic and cardiac contractile dysfunction in a murine model of 40% contact burn complicated by Streptococcus pneumoniae (1 x 10(5) CFU) sepsis. Male, 9- to 10-week-old C57/BL6 mice were divided into the following groups: sham burn, sham sepsis; 24 h after burn alone; 24 h after sepsis alone; 7 days after burn alone; and 7 days after burn followed by pneumonia sepsis. Hemodynamic and cardiac contractile function was assessed with carotid artery cannulation and left ventricular pressure-volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Although IL-6 is increased as part of the acute phase reaction, its role in mediating myocardial depression after acute injuries is not as clearly defined as the roles of TNF-␣ and IL-1␤. We focused on the role of IL-6 in cardiac inflammation and function after burn plus sepsis as a clinically relevant model of injury where our laboratory has repeatedly shown that myocardial depression after this two-hit injury is exaggerated compared with burn alone or sepsis alone (33,38,42,43).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although IL-6 is increased as part of the acute phase reaction, its role in mediating myocardial depression after acute injuries is not as clearly defined as the roles of TNF-␣ and IL-1␤. We focused on the role of IL-6 in cardiac inflammation and function after burn plus sepsis as a clinically relevant model of injury where our laboratory has repeatedly shown that myocardial depression after this two-hit injury is exaggerated compared with burn alone or sepsis alone (33,38,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Seven days after burn, mice were anesthetized again with isoflurane, and 1 ϫ 10 5 colony forming units of S. pneumoniae were instilled into the trachea. Sepsis was confirmed by positive blood cultures 24 h after bacterial instillation (38).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations